PKM: IRT PAKAIAN RAJUTAN DI KECAMATAN TABANAN KABUPATEN TABANAN PROVINSI BALI - Putu Pande Yudiastra; Gusti Ngurah Mega Nata (Ngayah: Majalah Aplikasi IPTEKS, 2019)
Tabanan tourism objects grow micro crafts in the city of Tabanan, such as the craft of "yarn knitting". Some groups of craftsmen who have produced the yarn knit are IRT Ni Wayan Mursiniati and IRT Ni Wayan Debby Suciawati. Both IRT craftsmen took the initiative to produce ferns and accessories from knitted yarn. The handicrafts from the two IRTs are in great demand by local, domestic tourists and foreign tourists visiting tourist attractions in the Tabanan area. So, then the two IRT craftsmen were made a service partners in the Community Partnership Program. The monthly interest of the two partners is quite large, where IRT partner Ni Wayan Mursiniati can achieve the highest turnover of up to 10 million per month with an average of 7 million per month, while Ni Wayan IRT Debby Suciawati can only achieve the highest turnover of 3 million per month with an average of 2 million per month. The partners' second profit can be 60% - 80%, from turnover because the operations and materials used by the two partners are not expensive. The number of workers from IRT partner Ni Wayan Mursiniati is 10 people, all of whom are housewives in their neighborhood and will increase if there is a large order, while IRT partner Ni Wayan Debby Suciawati has 3 members. When viewed from the start of the IRT partner Ni Wayan Mursiniati's efforts have started since 1999, while IRT partner Ni Wayan Debby Suciawati began her business in 2008. However, the partner has obstacles namely in marketing and production. In marketing both partners only have very narrow marketing and not too many know their production. So far their products are ordered by collectors, or leave them at souvenir shops. Meanwhile, in the knitting production process both partners have only relied on needles and hands in making yarn knits. In this service program the two partners hope to increase their production and marketing. And from the results of partner business observations, there were also things that needed to be improved, such as production equipment, financial management, motive design and marketing training. So, the purpose of this community service is to help solve the problems of the two partners so that they can increase the quantity and quality of their production, help make production management, financial management and help product marketing through ICT and also provide sustainable marketing tools. The output targets to be achieved through this activity are increasing knowledge in the field of 100% financial management, increasing production by 50%, increasing sales by 50% -70% and marketing more effectively. To achieve these outcomes, the methods that will be used are by applying technology in production, increasing management knowledge, and using ICT in marketing and promotion such as creating promotional websites. Training for business management and management improvement has been carried out 100%, website creation for improving marketing has been completed 100%.